Uji Efektivitas Ekstrak Etanol Daun Cincau Hijau (Cyclea barbata Miers) Terhadap Bakteri Staphylococcus aureus - Muchson Arrosyid; Sutaryono; Resia Muliana (Universitas Muhammadiyah Klaten, 2019)
Infection is a disease caused by bacteria. For Example of bacteria that can cause infection is bacteria Staphylococcus aureus. The development of traditional medicines derived from nature received the attention of people and the government. Green cincau leaves (Cyclea barbata Miers) is one of plants containing compound as antibacterial. The purpose of this study was to determine the effectiveness of the ethanol extract of green cincau leaves (Cyclea barbata Miers) and to determine the value of Minimum Inhibitory Concentration (MIC) on the growth of Staphylococcus aureus bacter. This research is a type of experimental research. Green cincau leaves (Cyclea barbata Miers) were extracted using maceration method with 96% ethanol obtained by rendering of 4.32% b/b. Microbiology tests use the paper disc diffusion method. Green cincau leaf extract (Cyclea barbata Miers) was made into 3 concentrations namely 25%, 50%, 75% and negative controls using aquadestilata. The results of the research on ethanol extract of green cincau leaves (Cyclea barbata Miers) effectively inhibited the growth of Staphylococcus aureus bacteria. The 50% concentration has an average of 13.20 mm. The concentration of 75% has an average of 15.99 mm. Statistical results show differences in all concentrations with negative aquadestilata controls.